Math, asked by shatishsoni402, 7 months ago

simplfy the expression (√11-√7) (√11+√7) ​

Answers

Answered by Anonymous
4

(√11-√7) (√11+√7)  \\  \\  = ( \sqrt{11} ) {}^{2}  - ( \sqrt{ 7} ) {}^{2}  \\  \\  = 11 - 7 \\  \\  = 4(ans)

Formula used:

(a + b {)}^{2} (a - b {)}^{2}  =  {a}^{2}  -  {b}^{2}

hope it helps!

Answered by Anonymous
35

\huge\textsf\red{QUESTION:}

simplfy the expression (√11-√7) (√11+√7)

\huge\textsf\green{ANSWER:}

\textsf\green{4}

\huge\textsf\blue{SOLUTION:}

\textsf{Step\:1:} Using (a - b)(a + b) = a² - b², simplify the product

\implies\textsf{√11² - √7²}

\textsf{Step\:2:} Reduce the index of the radical and exponent with 2

\implies\textsf{√11² - √7²}

\implies\textsf{11 - 7}

\textsf{Lastly:} Subtract the numbers

\implies\textsf{11 - 7}

\green\implies\textsf\green{4}

hope this help!

Similar questions